A study of attitude of teachers and students towards open book and closed book assessment - Dr.Mamta Gupta, Sonia Gujral (International Journal of Scientific Research and Management (IJSRM), 2017)
If an examination is to test the information that students have memorized, closed book examinations are appropriate, or if the examination is to test the skills of problem solving and critical thinking, then open book examinations are useful, in which students are allowed to consult their text books and class notes and printed documents. The purpose of this research is to study the attitude of teachers and students towards open book and closed book examination. For this purpose, a sample of 50 teachers and 100 students of CBSE schools were selected from Raipur. Self-made questionnaire was used to collect the relevant data. The results revealed that open book examination should be a part of assessment along with closed book examination as it enhances the thinking skills of the students.